2022
DOI: 10.1128/aac.00741-22
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling and Probability of Target Attainment of Ceftaroline in Brain and Soft Tissues

Abstract: Ceftaroline, approved to treat skin infections and pneumonia due to methicillin-resistant Staphylococcus aureus (MRSA), has been considered for the treatment of central nervous system (CNS) infections. A population pharmacokinetic (popPK) model was developed to describe ceftaroline soft tissue and cerebrospinal fluid (CSF) distributions and investigate the probability of target attainment (PTA) of the percentage of the dosing interval that the unbound drug concentration exceeded the MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The PK parameter estimates were in the range of previous population PK analyses involving healthy volunteers (CL 10.9 L/h vs. 10.7 L/h for CL CR_median = 120 mL/min/1.73 m 2 and age median = 28 years [ 17 ], 11.9 L/h for CL CR_median = 145 mL/min [ 11 ]; V total 23.1 L vs. 19.0 L [ 17 ], 24.9 L for TBW median = 74.5 kg [ 11 ]). The interindividual variability associated with clearance was 15.6% and was in line with other studies including healthy volunteers (16.4% [ 11 ], 18.4% [ 30 ]). Potential sources of variability include renal excretion, factors influencing saturable elimination, or other covariates.…”
Section: Discussionsupporting
confidence: 91%
“…The PK parameter estimates were in the range of previous population PK analyses involving healthy volunteers (CL 10.9 L/h vs. 10.7 L/h for CL CR_median = 120 mL/min/1.73 m 2 and age median = 28 years [ 17 ], 11.9 L/h for CL CR_median = 145 mL/min [ 11 ]; V total 23.1 L vs. 19.0 L [ 17 ], 24.9 L for TBW median = 74.5 kg [ 11 ]). The interindividual variability associated with clearance was 15.6% and was in line with other studies including healthy volunteers (16.4% [ 11 ], 18.4% [ 30 ]). Potential sources of variability include renal excretion, factors influencing saturable elimination, or other covariates.…”
Section: Discussionsupporting
confidence: 91%
“…Ceftaroline is one of the newer cephalosporins approved by the FDA and has a desirable extension of the beta-lactam spectrum of activity to include methicillin-resistant Staphylococcus aureus (MRSA). Ceftaroline has had limited evaluation for CNS infections but has been used off-label for this indication [ 70 ]. Similar to the other beta-lactams, it has low CNS penetration.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…Similar to the other beta-lactams, it has low CNS penetration. In a Monte Carlo simulation, Helfer et al found that ceftaroline had 90% predicted target attainment for fT > MIC of 28.8% with an MIC of 1 mg/L; this improved to 99.8% and 97.2% in the presence of inflammation when ceftaroline 600 mg was administered every 8 h and every 12 h, respectively [ 70 ].…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…Chauzy et al reported a mean of 9% in a series of 11 patients with external ventricular drain, but without meningeal inflammation [ 8 ]. However, this penetration can be enhanced with meningeal inflammation, as showed by Helfer et alt [ 9 ]. In fact, animal models of meningitis show variable rates from 15 to 51%.…”
Section: Casementioning
confidence: 99%